Enhanced procoagulant activity of platelets after chemotherapy in non-small cell lung cancer. Issue 8 (3rd August 2017) - Ma, Ruishuang; Bi, Yayan; Kou, Junjie; Zhou, Jin; Shi, Jialan
ABSTRACT: The procoagulant status of patients with non-small cell lung cancer (NSCLC) after chemotherapy is poorly characterized and the role of platelets in hypercoagulative state of NSCLC is unknown. The aim of this study was to evaluate the procoagulant activity (PCA) of platelets in NSCLC before and after chemotherapy. The subjects were 52 patients newly diagnosed with NSCLC. The patients had decreased clotting time compared with healthy subjects, and the thrombin-antithrombin complex increased 2.5-fold after chemotherapy. Platelets in the patients after chemotherapy had enhanced phosphatidylserine (PS) exposure, and shortened coagulation time as well as increased thrombin and fibrin formation of platelets compared with those before chemotherapy. Platelet-derived microparticles increased 2-fold at day 1 and peaked at day 2 post-chemotherapy. Treatment of cisplatin in vitro also resulted in upregulated intrinsic FXa and thrombin formation on platelets with a dose-dependent manner. Platelets treated with aspirin significantly decreased PCA. However, lactadherin blocked PS and inhibited the PCA approximately by 70%. Seven days after chemotherapy, PCA of platelets restored to the baseline as that before chemotherapy, indicating that within a week of chemotherapy patient platelets are highly procoagulant and effective intervention should be taken in case of thrombosis. Our results suggested that platelets after chemotherapy had elevated PCA and may contribute to the hypercoagulative state of NSCLC. Prophylactic anti-coagulant combined with anti-platelet therapy may play an inhibitory role in thrombotic complications in NSCLC.